The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3168/jds.2021-21277
|View full text |Cite
|
Sign up to set email alerts
|

Reducing greenhouse gas emissions through genetic selection in the Australian dairy industry

Abstract: This research explores possible options to reduce greenhouse gas (GHG) emissions in the Australian dairy industry by (1) including an environmental component in the national breeding program and (2) estimating the economic and environmental impacts of implementation of the subsequent indexes. A total of 12 possible selection indexes were considered. These indexes were developed to predict changes in gross per-animal methane production (using 3 scenarios depending on availability and efficacy of a direct methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Generally, the h 2 estimates for survival analysed as binary scores with a linear model were low in different breeds and across different countries (Sasaki 2013). However, the relative emphasis of survival is large in BPI (Byrne et al 2016) and is almost doubled in the SI due to its relationship with lowering methane emissions (Richardson et al 2022). Hence, improving the accuracy of genetic predictions could lead to greater genetic gain for survival, which has a large economic as well as environmental impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the h 2 estimates for survival analysed as binary scores with a linear model were low in different breeds and across different countries (Sasaki 2013). However, the relative emphasis of survival is large in BPI (Byrne et al 2016) and is almost doubled in the SI due to its relationship with lowering methane emissions (Richardson et al 2022). Hence, improving the accuracy of genetic predictions could lead to greater genetic gain for survival, which has a large economic as well as environmental impact.…”
Section: Discussionmentioning
confidence: 99%
“…Although survival has a high relative weight or percentage emphasis (~8%) in Australia's national selection index, namely, the balanced performance index (BPI), this weight was almost doubled (~13%) in the sustainability index (SI) launched nationally in Australia in 2022 (DataGene 2022a). The aim of the SI is to reduce methane emission intensity, which is achieved through increasing the relative emphasis on feed saved and survival traits compared with BPI (Pryce et al 2015;Richardson et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The first 'Shift' strategy was a national carbon price that aims to encourage producers and consumers to shift to low-carbon farming alternatives. Richardson et al [46] measured the effect of including a GHG sub-index into the national breeding program, against carbon prices ranging from AUD 150 to 1000 per t CO 2 e and high-and low-accuracy residual CH 4 traits. The results showed that the current low accuracy of CH 4 prediction would reduce CH 4 by 0%, 0.09%, 0.36%, and 0.71% with a carbon pricing of AUD 150, AUD 250, AUD 500, and AUD 1000 per t CO 2 e, respectively.…”
Section: 'Shift' Strategiesmentioning
confidence: 99%
“…Although CH 4 production increases as milk yield increases due to genetic selection ( Hossein‑Zadeh, 2022 ), the main should be on CH 4 intensity (g of CH 4 per unit of milk yield). Reducing CH 4 at the expense of milk yield, DMI, or sacrificing economic gains should be avoided ( Richardson et al, 2022 ; Króliczewska et al, 2023 ).…”
Section: Genetic Improvement and Ghgmentioning
confidence: 99%